2018
DOI: 10.1055/a-0749-5520
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolcharakteristika ausgewählter Druckluftvernebler für Erwachsene in Simulationsmodellen und Verneblung von Salbutamol

Abstract: Zusammenfassung Ziel Der Erfolg einer Inhalationstherapie wird durch Menge und Qualität des inhalierten Aerosols bestimmt. Die Auswahl eines Verneblers bedarf der Kenntnis der entsprechenden Aerosolcharakteristika. Methoden Die Aerosolperformance von 9 marktüblichen Druckluftverneblern wurde in vitro in 2 Simulationsmodellen geprüft. Salbutamol (Sultanol forte® Fertiginhalat 2,5 mg/2,5 ml; GSK) wurde über 4 Minuten vernebelt. Die Outputparameter wurden mit dem Atemzugsimulator PARI Compas I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Secondly, since we believe that the dead volume of the nebulization cup has a great impact; different models or brands of nebulization devices with different dead volumes or different properties may produce different results in terms of aerosol parameters. Several studies have demonstrated that different nebulizer cups affect the character of the produced aerosol significantly, not only because of the dead volume but also because of the design and construction [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, since we believe that the dead volume of the nebulization cup has a great impact; different models or brands of nebulization devices with different dead volumes or different properties may produce different results in terms of aerosol parameters. Several studies have demonstrated that different nebulizer cups affect the character of the produced aerosol significantly, not only because of the dead volume but also because of the design and construction [34][35][36].…”
Section: Discussionmentioning
confidence: 99%